Non-susceptibility of Escherichia coli, Klebsiella spp., Pseudomonas spp., Streptococcus pneumoniae and Staphylococcus aureus in the UK: temporal trends in England, Northern Ireland, Scotland and Wales. (17th February 2016) - Guy, Rebecca; Geoghegan, Lourda; Heginbothom, Maggie; Howe, Robin; Muller-Pebody, Berit; Reilly, Jacqui S.; Wilson, Julie; Wiuff, Camilla; Wyatt, Tim; Johnson, Alan P.
Abstract: Objectives: To monitor and compare trends in the non-susceptibility of bloodstream isolates of pathogens to key antibiotics in the constituent countries of the UK between 2010 and 2014. Methods: Routinely generated antibiotic susceptibility test results for bloodstream isolates of Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Pseudomonas spp., Streptococcus pneumoniae and Staphylococcus aureus were collected from hospital microbiology laboratories in each country. Results: With the exception of a decrease in the proportion of S. aureus that were MRSA, non-susceptibility to key antibiotics among the pathogens studied remained largely unchanged over the 5 year study period, with any increases in non-susceptibility being small. Although some intercountry variation in the proportions of non-susceptible isolates was seen, apart from MRSA, the differences were generally small (<5%) and fluctuated from year to year, with no country showing consistently higher or lower rates of resistance. Conclusions: Collaboration between the constituent countries of the UK allows an integrated approach to nationwide surveillance of antibiotic resistance.